(untitled) (Bangladesh Journal of Microbiology, 2019)
Environmental Escherichia albertii strain DM104 has been found to induce protective immunity against Shigella dysenteriae in guinea pig model and intranasal immunization showed promising results in terms of antibody response and protective efficacy. For selecting a proper immunodiagnostics marker against shigellosis, the current study investigated the antigenic cross-reactivity between DM104 and four different Shigella spp (S. dysenteriae type 4, S. flexneri type 2a, S. boydii type 15 and S. sonnei). At least six antigenic protein bands (85, 72, 34, 30, 23 and 20 k Da) of the surface components from all these species reacted strongly with both homologous and heterologous antisera, suggesting common distribution of antigenic determinants/epitopes in these bacterial species. This experiment, thus gave a clear idea of the level of antigenic determinants/epitopes sharing and variations between the DM104 and four Shigella spp. Results from this study suggest that the 34, 23 and 20 k Da antigenic proteins may be incorporated as immunodiagnostic marker for the detection of different Shigella spp. Bangladesh J Microbiol, Volume 35 Number 1 June 2018, pp 17-21